2022
DOI: 10.3389/fimmu.2022.881655
|View full text |Cite
|
Sign up to set email alerts
|

Allergen-Specific IgA Antibodies Block IgE-Mediated Activation of Mast Cells and Basophils

Abstract: Mast cells and basophils have long been implicated in the pathogenesis of IgE-mediated hypersensitivity reactions. They express the high-affinity IgE receptor, FcϵRI, on their surface. Antigen-induced crosslinking of IgE antibodies bound to that receptor triggers a signaling cascade that results in activation, leading to the release of an array of preformed vasoactive mediators and rapidly synthesized lipids, as well as the de novo production of inflammatory cytokines. In addition to bearing activating recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 39 publications
3
20
0
Order By: Relevance
“…In line with this, levels of total IgE, the pivotal immunoglobulin involved in type I allergy reactions 33 , as well as total levels of IgG in serum and intestinal homogenates of the peach allergic mice were strongly enhanced. In contrast, total IgA levels were significantly decreased in the serum, correlating with reports of a protective role of IgA in allergic diseases by inhibition of IgE-induced mast cell degranulation and cytokine production 34,35 .…”
Section: Discussionsupporting
confidence: 85%
“…In line with this, levels of total IgE, the pivotal immunoglobulin involved in type I allergy reactions 33 , as well as total levels of IgG in serum and intestinal homogenates of the peach allergic mice were strongly enhanced. In contrast, total IgA levels were significantly decreased in the serum, correlating with reports of a protective role of IgA in allergic diseases by inhibition of IgE-induced mast cell degranulation and cytokine production 34,35 .…”
Section: Discussionsupporting
confidence: 85%
“…Other studies still need to be performed to comprehend the role of the various immune cell types as well as cytokines and immunoglobulins involved in this process through time. For instance, IgA evaluation was not possible during this work, but previous data from our group as well as in the literature suggest this immunoglobulin may play a significant role in our mouse model [88]. Here, we confirmed that a bystander suppression may occur when the animals were offered the allergenic food associated to the ingestion of tolerogenic food (mouse chow).…”
Section: Discussionsupporting
confidence: 84%
“…FcεRI‐mediated activation of mast cells and basophils leads to the immediate release of granular pro‐inflammatory preformed mediators and to neosynthesis and release of arachidonic derivatives, cytokines, and chemokines 18 . These effects can be toned down through co‐engagement of FcγRIIB (CD32B) or other inhibitory receptors that can block degranulation and decrease cytokine production 19,20 …”
Section: Introductionmentioning
confidence: 99%
“…18 These effects can be toned down through co-engagement of FcγRIIB (CD32B) or other inhibitory receptors that can block degranulation and decrease cytokine production. 19,20 The lower affinity IgE receptor FcεRII (CD23, Kd ≈ 10 −7 -10 −8 M) is mainly expressed by some subsets of B cells and monocytes and is involved in the regulation of IgE synthesis and, together with FcεRI, in IgE-mediated facilitated antigen presentation. 14 Beyond its effects on IgE synthesis, little is known about CD23-mediated pathogenicity of IgE in AbAID.…”
Section: Introductionmentioning
confidence: 99%